Analisis Faktor Risiko Ketuban Pecah Dini di Rumah Sakit Umum Bahteramas - Heny Hastuti; I Putu Sudayasa; Juminten Saimin (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2016)
Premature rupture of membrane (PROM) is an important issue in the obstetric-related difficulty premature birth and the occurrence of infections which increases morbidity and perinatal mortality and cause an infection in the mother, therefore treatment PROM requires action that is detailed so that it can decrease the incidence of labor prematuritas and infection in the uterus. This research aims to analyze the risk factors associated with the incidence of PROM in RSU Bahteramas. This type of research is observational analytic study with nested case control design. This research was conducted in RSU Bahteramas and on research using secondary data, namely medical record of the patient. The sample in this research is the mother who experienced PROM and sample control on research this is a mother who experienced the birth normal delivery. Total sample of 178 sample consisting of  89sample cases and 89 the sample control. The data were analyzed using Odds Ratio test. The results showed that maternal age is a risk factor for the incidence of PROM with OR = 4.95 (2,52-9.72; 95%), maternal parity is a risk factors with OR = 9.94 (4.44-22, 24; 95%), education level is a risk factors with OR = 2.43 (1,32-4.49; 95%) and Gemelli was not a risk factor of PROM with the OR = 2.61 (7.77-0.88; 95%).Maternal age, Maternal Parity and education level is a risk factors in the incidence of PROM and gemelli is not a risk factor for incident PROM in RSU Bahteramas from January 2013 – December 2014.Keywords: PROM, Maternal age, maternal parity, education level and Gemelli.